Synthesis of Compositional Microprogram Control Unitsfor Programmable Devices - Wiśniewski, Remigiusz
The dissertation focuses on the structural decomposition of control units. There are six new synthesis methods of compositional microprogram control units introduced. Proposed solutions can be divided into two main groups. The first one deals with CMCUs with mutual memory, where the internal code of the controller is recognized by an address of microinstruction. The second group of presented methods bases on the control units with sharing codes, where the microinstruction address is formed as a concatenation of codes generated by the counter and by the register. The aim of all proposed solutions is reduction of the number oflogic blocks ofthe destination programmable device.
Keywords: synteza; jednostka sterująca; układ programowalny; implementacja; mikroprogramowany układ sterujący